(untitled) (Per Musi, 2021)
This article analyzes Arthur Kampela’s Percussion Studies IV and V, where the guitarist’s technique and posture are transposed to the guitar. Both pieces deal with and question the guitar technique, blending characteristic fingerings with the use of a metal bow. The works are understood within a gestural perspective, where sound and gesture, the instrumentalist and the instrument coexist within a physical relationship. Tapping Technique, emancipation between hands, Air Guitar, and the idea of ​​music without sound are studied. Scientific proposals in favor of a corporal understanding of the musical practice are reviewed: the guitar technique according to Hubert Käppel, the visible music of Dieter Schnebel, besides studies about the gesture (Gritten and King, Godoy and Leman, Delalande, Cox, Oberhaus and Stange…). The study culminates in an attempt to understand the way the instrumentalist becomes the core of the composition.